2021
DOI: 10.1108/bpmj-07-2020-0335
|View full text |Cite|
|
Sign up to set email alerts
|

Organizational performance and capabilities to analyze big data: do the ambidexterity and business value of big data analytics matter?

Abstract: PurposeThe aim of the study is to examine the impact of the big data analytics capabilities (BDAC) on the organizational performance. The study also examines the mediating role of ambidexterity and the moderating role of business value of big data (BVBD) analytics in the relationship between the big data analytics capabilities and the organizational performance.Design/methodology/approachThis study collected primary data based on a questionnaire survey among the large manufacturing firms operating in UAE. A to… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(81 citation statements)
references
References 67 publications
3
18
0
Order By: Relevance
“…Hence, we expect not just a direct impact of SCA on OP but also an indirect effect of SCA in the BI-OP relationship. This finds support from prior studies (Aljumah et al, 2021;Pertheban and Arokiasamy, 2019;Chams-Anturi et al, 2019;Belhadi et al, 2021;Zhao et al, 2021;Al-khawaldah et al, 2022), which indicated that organizational ambidexterity plays an indirect role in improving the performance of firms. This study based on the contradictory views expressed re-examines the relationship by posing the third and fourth hypotheses.…”
Section: Effect Of Business Intelligence On Operational Performancesupporting
confidence: 81%
See 2 more Smart Citations
“…Hence, we expect not just a direct impact of SCA on OP but also an indirect effect of SCA in the BI-OP relationship. This finds support from prior studies (Aljumah et al, 2021;Pertheban and Arokiasamy, 2019;Chams-Anturi et al, 2019;Belhadi et al, 2021;Zhao et al, 2021;Al-khawaldah et al, 2022), which indicated that organizational ambidexterity plays an indirect role in improving the performance of firms. This study based on the contradictory views expressed re-examines the relationship by posing the third and fourth hypotheses.…”
Section: Effect Of Business Intelligence On Operational Performancesupporting
confidence: 81%
“…Prior studies (Aljumah et al, 2021;Alamsjah and Asrol, 2022;Belhadi et al, 2021) have argued that managers often face trade-offs between flexibility and efficiency, where giving preference to one over the other is detrimental. Contrarily, others believe that firms can pursue both strategies, flexibility and efficiency, by developing an ambidexterity capability (Ojha et al, 2018;Aslam et al, 2018;Zhao et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several of the reviewed articles develop and empirically test research models that combine business analytics capability with different valuable, rare, and difficult to imitate resources and capabilities, which have theoretically significant roles in translating business analytics into improved firm performance. For instance, recent research highlights the complementary roles of dynamic capabilities (e.g., Wamba et al, 2017;Mikalef et al, 2020), business strategy alignment (Akter et al, 2016;Wamba et al, 2019), organizational culture (Behl, 2020;Upadhyay and Kumar, 2020), information technology capital, educated workers, high flow-efficiency production workplaces (Brynjolfsson et al, 2021), knowledge management (Ferraris et al, 2019, Shabbir andGardezi, 2020), ambidexterity (Božič and Dimovski, 2019;Rialti et al, 2019;Aljumah et al, 2021), big data analytics management capabilities (Razaghi and Shokouhyar, 2021), and resource orchestration and circular economy implementation (Kristoffersen et al, 2021). In addition, business analytics positively influences firm performance through mediating outputs, such as informational benefits (Asadi Someh and Shanks, 2015), information quality (Ashrafi et al, 2019), technological innovation (Saleem et al, 2019), product and process innovation (Saleem et al, 2020), dual innovations (Su et al, 2020), sustainable product development (Ali et al, 2020), business process performance (Aydiner et al, 2019), business decision making (Chatterjee et al, 2021), and functional performance (Torres et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…To sustain competitive advantages, they must be agile and flexible enough to reconfigure their resources and skills in rapidly evolving conditions (Teece et al, 1997). DCV, as one of the most significant views in strategic management, provides organizations with perspectives to facilitate comprehending how dynamic capabilities could improve organizational resilience in adverse circumstances (Aljumah et al, 2021). Therefore, DCV is adopted as the grounded theory of the research, which justifies the necessity and appropriateness in linking BDAC and ambidexterity in the banking sector.…”
mentioning
confidence: 99%